2022
DOI: 10.3389/feart.2022.1029160
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning opportunities to conduct high-fidelity earthquake simulations in multi-scale heterogeneous geology

Abstract: The 2019 Le Teil earthquake is an illustrative example of a moderate (MW 4.9) yet damaging event, occurring at shallow depth (≈1 km) in a region with little to no geophysical data available. Therefore, using a high-fidelity wave propagation code, we performed numerical simulations of the Le Teil earthquake in a highly uncertain framework, investigating several seismic sources and geological set-ups. With respect to the former aspect, a point-source model and an extended kinematic fault model were compared. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…The geological database was used to study dimensionality reduction methods such as the PCA and a 3D autoencoder (Lehmann et al, 2022). It was shown that at least 1000 PCA components should be preserved to reconstruct a geological model whose heterogeneities are not too smoothed.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geological database was used to study dimensionality reduction methods such as the PCA and a 3D autoencoder (Lehmann et al, 2022). It was shown that at least 1000 PCA components should be preserved to reconstruct a geological model whose heterogeneities are not too smoothed.…”
Section: Applicationsmentioning
confidence: 99%
“…Since extensive geophysical investigations are needed to obtain 3D geological models, they are rare, and when existing, they are still limited by epistemic uncertainties. Therefore, when trying to reproduce an earthquake with physics-based numerical simulations, uncertainties can be represented by random heterogeneities added to the reference model to introduce variability (Chaljub et al, 2021;Lehmann et al, 2022).…”
mentioning
confidence: 99%
“…Our geological database represents 3D S-wave velocity fields in a 9.6 km × 9.6 km × 9.6 km cube. This database is built from layered random fields to provide a general decomposition basis to any 3D material [30]. Each geology contains a homogeneous bottom layer with constant velocity V S =4500 m/s.…”
Section: Geological Databasementioning
confidence: 99%